Digital Licensing Regulations in Indonesia: Legal Study and Policy Implementation - Didi Nursidi (International Journal of Science Education and Cultural Studies, 2024)
Current advances in information technology have had complex impacts, particularly in the realm of human rights and licensing. These challenges include the enforcement of intellectual property rights (IPR) laws, and the lack of synchronization between top-down and bottom-up regulations, leading to disharmony between national regulations and the needs of the local digital ecosystem. This study aims to explore the digital licensing regulatory framework in Indonesia with a focus on implementation in West Java, identify legal gaps, and formulate an adaptive regulatory model appropriate to the local context. The study uses an empirical legal approach with analysis of primary and secondary legal documents, in-depth interviews with 45 intellectual property rights law experts, regulators, and digital industry players in West Java, and focus group discussions (FGDs) to validate the findings. Data were analyzed using a thematic analysis framework and local context-based regulatory analysis. The findings indicate that the implementation of digital licensing regulations in West Java faces multiple challenges, including weak law enforcement infrastructure at the district/city level, disparity in human resource capacity between Bandung as the center and its outlying areas, and low digital literacy among local creative industry players. This research produces a locally context-based adaptive regulatory model that can serve as a policy reference for local governments in formulating a comprehensive and responsive digital licensing legal framework.